2012
DOI: 10.1136/annrheumdis-2011-201178
|View full text |Cite
|
Sign up to set email alerts
|

Association of atherosclerosis with presence and progression of osteoarthritis: the Rotterdam Study

Abstract: This study showed independent associations of atherosclerosis with osteoarthritis of the knee and hand joints in women. The evidence was most solid for a relation with DIP osteoarthritis. More research is needed to confirm the associations and examine the differential association with various joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 35 publications
8
99
1
1
Order By: Relevance
“…Previous studies have reported associations between vascular pathology and the risk of OA [4][5][6], with vascular pathology assessed by different markers including artery vessel wall thickness [4][5][6], carotid plaque [4,5], coronary and aortic calcifications [5]. Only one prospective cohort study examined the association between vascular pathology and the risk of knee OA [4].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have reported associations between vascular pathology and the risk of OA [4][5][6], with vascular pathology assessed by different markers including artery vessel wall thickness [4][5][6], carotid plaque [4,5], coronary and aortic calcifications [5]. Only one prospective cohort study examined the association between vascular pathology and the risk of knee OA [4].…”
Section: Discussionmentioning
confidence: 98%
“…Only one prospective cohort study examined the association between vascular pathology and the risk of knee OA [4]. It was found in the Rotterdam Study that greater carotid intima media thickness was associated with increased prevalence of radiographic knee OA in women only, with no association seen for the progression of knee OA [4].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…ANGPTL4 encodes a secreted protein of the angiopoietin family involved in angiogenesis (18). ANGPTL4 transcript localizes to stromal fibroblast-like cells adjacent to blood vessels in the mouse arthritic tissue (14). ICAM1 is expressed by many cell types, including fibroblasts, endothelial cells, some leukocytes, and also on the surface of osteoblasts (62).…”
Section: Biological Functions and Canonical Pathways Of De Genesmentioning
confidence: 99%
“…GWAS, genome-wide association study. inflammatory pathophysiology (14). Several DE genes in both angiogenesis and atherosclerosis likely affect expression of genes contributing to OC, such as metalloproteinase 3 (MMP3) and platelet-derived growth factor alpha polypeptide (PDGFA).…”
Section: Biological Functions and Canonical Pathways Of De Genesmentioning
confidence: 99%